2002
DOI: 10.1046/j.1439-0442.2002.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Observations of the Uterine Regression in the Ewe under Different Obstetrical Conditions

Abstract: Involution of the ovine uterus after parturition was studied using real-time B-mode ultrasonography. The diameter of the uterus, the uterine lumen and the caruncles were investigated during the first 30 days post-parturition (p.p.) by transrectal and transabdominal application of the ultrasound probe. Ewes that spontaneously delivered showed a physiological regression of the uterus with a transversal diameter of 4.9 (+/- 0.86) cm on day 1 p.p. which decreased to 1.84 (+/- 0.14) cm until day 30. The course of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
2
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 13 publications
10
56
2
11
Order By: Relevance
“…In comparison with sheep, most studies reported slower involution and found that the uterine regression in ewes finished approximately after 30 days PP (Hayder and Ali, 2008;Rubianes and Ungerfeld, 1993), in contrast to other authors which observed the end of the uterine regression in sheep by day 17 PP (Hauser and Bostedt, 2002).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In comparison with sheep, most studies reported slower involution and found that the uterine regression in ewes finished approximately after 30 days PP (Hayder and Ali, 2008;Rubianes and Ungerfeld, 1993), in contrast to other authors which observed the end of the uterine regression in sheep by day 17 PP (Hauser and Bostedt, 2002).…”
Section: Resultsmentioning
confidence: 78%
“…In ewes, Hauser and Bostedt (2002) described the course of uterine regression by exponential function as:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hauser and Bostedt (2002) analyzed the diameter of the uterine lumen and caruncles during the first 30 days post-partum in German Lend sheep and concluded that involution is completed at approximately day 17 after lambing, and later in animals that have been subjected to obstetric intervention, cesarean delivery, and retention of fetal membranes. In Santa Inês sheep, Nasciutti et al (2012) evaluated clinical features of uterine involution and determined a complete involution up to 28 days postpartum.…”
Section: Resultsmentioning
confidence: 99%